LOCAL CULINARY DEVELOPMENT STRATEGY AS A TOURIST ATTRACTION IN YOGYAKARTA - Wachyuni, Suci Sandi; Saputro, Yudha Dwi (International Conference on Cultural Studies, 2019)
Local Culinary Development Strategy as a Tourist Attraction in D.I Yogyakarta. This arrangement aims to answer the question in this study to find out local tourist perceptions about local culinary in D.I Yogyakarta, and the strategy of local culinary development as a tourist attraction. This research methodology is qualitative research. The collection data for this study used direct field observations, interviews and documentation studies, while data analysis used a SWOT matrix for getting alternative strategies. Respondents in this study amounted to 12 people consisting of the regional tourism government, culinary entrepreneurs, and local tourists. In the pre-study, researchers conducted a survey of local tourist’s perceptions of local culinary for 20 local tourists. The results showed that the perception of local culinary in the D.I Yogyakarta in general was good in the indicators of traditional food quality, traditional food portions, menu variations, traditional food hygiene, traditional presentation, traditional food prices, service quality, eating place atmosphere, and provision of entertainment in eating places. The results of the SWOT analysis show a number of alternative strategies that can be applied in developing local culinary in D.I Yogyakarta. There are divided by four strategy. The first one is SO (Strength-Opportunity) strategy is selling traditional food at tourist attractions, airports, and stations. The WO (Weakness-Opportunity) strategy is infrastructure development, culinary product innovation, and promotion. ST (Strength-Threats) strategy is to develop culinary place more comfortable and maintain local culinary quality. And for the WT (Weakness-Threat) strategy, product diversification adjusts to trends, enhances culinary facilities, and increases human resources in the culinary sector. The conclusion that can be taken is that local culinary can be one of the attractions in the tourism sector in Yogyakarta. But it needs to be developed more in order to attract tourists to come to D.I Yogyakarta.